Revisiting Gadamer’s Conception of Works of Art - Szeto, Man Chun (Labyrinth, 2021)
In contrast to Kant's aesthetic, Gadamer proposes a fundamentally different way of understanding our experiences of art. One that is not restricted by the dichotomy between subjectivity and objectivity: A work of art is not simply an object created by an artist, but a "world" in which all the "players" participate. This conception of art is inspired by the performing arts; but how much is it relevant to other forms of art? Gadamer never explored this question fully. It is of interest, therefore, to expand the analysis of Gadamer on two fronts: first, new forms of art such as installations and video games; second, artistic practices in East Asia, notably, the Japanese art of kintsugi and Chinese art of seals (zhāng). The analysis of these forms of art not only helps broaden the scope of Gadamer's theory, but shows also that the insights found in his works are more relevant than ever.